Traumatic Ulcer in a Patient with Class I Malocclusion of Angle Type 1: A Case Report - Intan Wijayanthy; Atia N. Sidiqa (e-GiGi, 2022)
Abstract: Malocclusion can cause oral problems inter alia traumatic ulcers. The clinical appearance of traumatic ulcers is non-specific depending on the etiology. The ulcer has a smooth surface, yellowish base and red margin, and no induration. We reported a case of traumatic ulcer associated with class I malocclusion of Angle type I. The chief complaint was a sore lesion on the left part of the inner lower lip since two days ago due to being bitten while eating. Based on the anamnesis and clinical examination, the diagnosis of this case was traumatic ulcer with a predisposing factor of class I malocclusion of Angle type I. The management of this case was application of a covering agent, an antiseptic mouthwash, multivitamin consumption, and orthodontic treatments to manage the malocclusion in preventing the recurrence of the traumatic ulcer. In conclusion, the management of a traumatic ulcer case requires attention to the overall condition of the oral cavity by considering all the predisposition factors. Dentists must be able to recognize and to manage such case properly.Keywords: malocclusion; traumatic ulcerÂ Â Abstrak: Maloklusi dapat menyebabkan masalah rongga mulut, salah satunya ulkus traumatik. Gambaran klinis ulkus traumatik bentuknya tidak spesifik tergantung pada etiologinya. Ulkus memiliki permukaan halus, dasar lesi berwarna kekuningan dengan margin merah, serta tidak terdapat indurasi. Kami melaporkan kasus seorang pasien dengan ulkus traumatik disertai maloklusi kelas I tipe I Angle. Pasien datang dengan keluhan terdapat sariawan pada bibir bawah bagian dalam kiri sejak dua hari lalu karena tergigit saat sedang makan. Dari hasil anamnesis dan pemeriksaan klinis, didapatkan diagnosis penyakit pasien ini ialah ulkus traumatik dengan faktor predisposisi maloklusi kelas I tipe I Angle. Penatalaksanaan kasus ini menggunakan covering agent, obat kumur antiseptik, multivitamin, serta serangkaian perawatan ortodontik untuk mencegah rekurensi ulkus traumatik. Simpulan studi ini ialah penatalaksanaan kasus ulkus traumatik memerlukan perhatian terhadap keadaan rongga mulut pasien secara menyeluruh dengan mempertimbangkan segala factor predisposisi. Dokter gigi harus mampu mengenali dan menangani kasus demikian secara tepat.Kata kunci: maloklusi; ulkus traumatik